2008
DOI: 10.1007/s10157-007-0003-8
|View full text |Cite
|
Sign up to set email alerts
|

Applications of LDL-apheresis in nephrology

Abstract: LDL-apheresis (LA) was originally used for familial hyperlipidemia, and then in Japan extended to use for the treatment of patients with peripheral arterial disease (PAD) and nephrotic syndrome due to steroid-resistant focal glomerular sclerosis (FGS). The reason why this treatment is applicable for these disorders is due to the fact that LA exerts its favorable effects beyond the lipid-lowering effect. The main underlying mechanisms, for example, in the case of LA application in patients with PAD are: (1) imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 59 publications
1
36
1
Order By: Relevance
“…Hattori et al [8] reported that LDL-A and prednisolone therapy provided complete remission in 5 of 11 pediatric patients with steroidresistant primary FSGS (median age at disease onset, 12 years; range, 7 to 14 years). Although the mechanism of the benefi cial effects of LDL-A in patients with NS is unclear, some experiments have revealed that a reduction in oxidized LDL reduced infl ammatory cytokines and chemokines and suppressed macrophage invasion into glomeruli or interstitium [7,11]. It was also reported that the adsorption of unknown factors by dextran sulfate alleviated the hypercoagulability and renal vasoconstriction [7,11].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Hattori et al [8] reported that LDL-A and prednisolone therapy provided complete remission in 5 of 11 pediatric patients with steroidresistant primary FSGS (median age at disease onset, 12 years; range, 7 to 14 years). Although the mechanism of the benefi cial effects of LDL-A in patients with NS is unclear, some experiments have revealed that a reduction in oxidized LDL reduced infl ammatory cytokines and chemokines and suppressed macrophage invasion into glomeruli or interstitium [7,11]. It was also reported that the adsorption of unknown factors by dextran sulfate alleviated the hypercoagulability and renal vasoconstriction [7,11].…”
Section: Discussionmentioning
confidence: 95%
“…Although the mechanism of the benefi cial effects of LDL-A in patients with NS is unclear, some experiments have revealed that a reduction in oxidized LDL reduced infl ammatory cytokines and chemokines and suppressed macrophage invasion into glomeruli or interstitium [7,11]. It was also reported that the adsorption of unknown factors by dextran sulfate alleviated the hypercoagulability and renal vasoconstriction [7,11]. Another possible mechanism is the enhancement of corticosteroid or CyA response by changing drug interactions after lipid removal [6,8,11].…”
Section: Discussionmentioning
confidence: 97%
“…It is intriguing to note that in terms of pharmacodynamics, LDLA improves steroid and cyclosporine uptake into lymphocytes. 18) Moreover, in patients with peripheral arterial occlusive disease, serum levels in VEGF statistically increased after 10 sessions of LDLA, and further increased up 3 months after a completion of this intervention. After 10-times therapy, IGF-I significantly decreased (p<0.05), but increased over the basal value 3 months after this therapy.…”
Section: Bypass Grafting Endovascular Therapymentioning
confidence: 91%
“…The main underlying mechanisms, for example, in the case of LDLA application in patients with PAD are: (1) improvement of hemorheology, (2) improvement of endothelial dysfunction, (3) elevations of serum levels of NO and bradykinin, (4) increase in serum levels of vascular endothelial growth factor, and (5) reduction of adhesion molecules on monocytes. 18) Massive proteinuria is also an important challenge in nephrology. The possible mechanisms besides removal of toxic lipids are the reduction of the vasoconstrictive prostanoid and TXA 2 and an improvement in macrophage function evidenced by a significant amelioration of interleukin-8 production by LPS-stimulated peripheral blood mononuclear cells.…”
Section: Bypass Grafting Endovascular Therapymentioning
confidence: 99%
“…However, the obstruction or improvement of peripheral circulation is not always parallel to patients' symptom [5,6]. Kobayshi summarized the several mechanisms of LDL-A [7]: (1) direct effect of lowered lipids or reduction of lipid toxicity; (2) improvement of hemorpheology by removing fibrinogen; (3) vasodilatory effects by an increase in VEGF/NO/bradykinin production/endothelium-derived vasodilatory factors or IGF-I or a decrease in thromboxane A2 [8,9]; (4) reduction of circulating vascular permeability factors; (5) anti-inflammatory effects-reduction of oxidized LDL, P-selectin, CRP, and ICAM-1 [10,11]; (6) improvement of endothelial dysfunction [12]; and (7) enhancement of corticosteroids or cyclosporine response by changing drug interactions following lipid removal. However, the point is that we have not found a definite quantitative marker to suggest the long-term and prolonged therapeutic effects of LDL-A treatment on PAD in dialysis patients.…”
Section: Introductionmentioning
confidence: 99%